2020
DOI: 10.1002/pssb.202000150
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Studies on the Deformation of Missing‐Rib and Mixed Structures under Compression

Abstract: Auxetic materials are an active research area with many potential applications. [1-8] There are many mechanisms/structures that have been developed to generate negative Poisson's ratio behaviors, including re-entrant structures, chiral structures, rotating rigid/semirigid units and angle-ply laminates. [7-15] These established mechanisms and the capacity of designing Poisson's ratio through controlled heterogeneity have opened up the possibility of developing material systems with targeted Poisson's ratios. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Patterns that possess a negative Poisson's ratio, such as re-entrant, rotational, chiral, and crumpled sheets, can be used for this purpose. The missing-rib structure was chosen because it divided the pattern into rows and columns and allowed for its systematic design and modification [61][62][63][64]. We demonstrated the fabrication of expandable structural electronics via multi-material printing, such as capacitor-type strain sensors and resistor-type heaters.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns that possess a negative Poisson's ratio, such as re-entrant, rotational, chiral, and crumpled sheets, can be used for this purpose. The missing-rib structure was chosen because it divided the pattern into rows and columns and allowed for its systematic design and modification [61][62][63][64]. We demonstrated the fabrication of expandable structural electronics via multi-material printing, such as capacitor-type strain sensors and resistor-type heaters.…”
Section: Discussionmentioning
confidence: 99%
“…Several structures have been used to mimic auxetic behaviour in the microscopic and macroscopic scales. Some of them include re-entrant honeycomb structures, 7-10 missing-rib structures, [11][12][13][14] chiral structures, [15][16][17][18] and arrowhead structures, [19][20][21][22] among many others. In addition, unconventional and highlytailored structures have also been researched extensively to obtain highly specific requirements for the intended application.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their wide usage, these structures have been extensively altered in terms of their geometrical constraints and structural members to extract maximum functionality in recent times. Studies by Tang et al 13 to assess the effects of sample sizes and strain rates on the NPR stability of missing-rib structures showed that the deformation and the instability of the structures resulted from the contact among corner-edge walls. The study proposed a mixed model approach to improve the stable auxeticity range and shape retention.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses resulted in different deformation patterns and stability strain ranges for the varied shapes and sizes of the chiral auxetic models. [ 59 ] The mechanical responses of a chiral shape structure were evaluated extensively for the varied compressive loading velocities. The high strain rate of loading resulted in an enhanced specific strength and shock absorbance as compared with quasistatic (slow strain rate) loading.…”
Section: Introductionmentioning
confidence: 99%